New Insights on the Compatibility of Nitrocellulose with Aniline‐Based Compounds. Issue 8 (28th May 2019) - Trache, Djalal; Tarchoun, Ahmed Fouzi; Chelouche, Salim; Khimeche, Kamel
Abstract: In this paper, the compatibility of nitrocellulose (NC) with some aniline‐based stabilizers was studied in order to detect any interaction between these materials. Both thermal techniques [differential scanning calorimetry (DSC) and vacuum stability test (VST)], and supplementary non‐thermal techniques [Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD) and densimetry] were used. The thermal and non‐thermal measurements showed that NC was highly compatible with N‐(2‐methoxyethyl)‐p‐nitroaniline (MENA) and diphenylamine (DPA), while a degree of incompatibility is indicated for N‐(2‐acetoxymethyl)‐p‐nitroaniline (ANA). The compatibility of the different mixtures was further probed by the kinetic investigation, and the activation energy and the pre‐exponential factors were computed. A detailed discussion and comparison of the compatibility results from all the methods are made. Abstract :